Subproportion control of double input buck converter for fuel cell/battery hybrid power supply system - Wang, Gucheng (2015)
Characterised with more integrated topology, simpler manipulations, less component count, and comparative higher efficiency, multiple-input converters (MICs) become an attractive candidate in renewable energy hybrid systems (REHSs). To seamlessly and smoothly transit from one operating mode to another is one of the critical issues that the energy management strategy should concern about. Normally, the mode transition (MT) design is usually required for the auxiliary circuits and components, which runs opposite to the MIC's intrinsic advantages and may cause potential problems for the system's reliability and stability. The subproportion control (SPC) approach presented in this study combines two operating modes into a sole control algorithm module without any hardware assistance. The so-called subproportion (SP) term is an additional control variable served as a certain proportion of the voltage-regulation duty cycle, dv. The product of SP and dv composes the duty cycle for current limitation of the first power source, beyond which, a seamless and smooth MT can be automatically and spontaneously implemented. The small-signal modelling for the three most-commonly-used topologies in the MIC family showed SPC's universal applicability. It was employed onto a 1 kW double-input-buck-converter-based fuel cells/battery REHS prototype for the verification of its control performance and auto-MT capability.